Perbandingan Pengaturan Passing Off dalam Hukum Indonesia dan Amerika Serikat: Analisis Kasus MS Glow vs PS Glow - Eva Aria Angelina; Kukuh Tejomurti (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
This research aims to analyze the comparison of passing off regulations in Indonesian and United States trademark laws, which is motivated by the rampant practice of passing off in Indonesia, as illustrated in the case of MS Glow vs PS Glow. The United States is a comparative reference because it has a well-established doctrine of passing off. The method used is normative juridical with a literature study approach, referring to Law Number 20 of 2016 concerning Trademarks and Geographical Indications and Decision Number 160 K/Pdt.sus-HKI/2023. The results of this study show that the Indonesian Trademark Law does not explicitly regulate passing off so that the protection of the goodwill of business actors is not comprehensive, as evidenced in the case of MS Glow vs PS Glow where the court cannot order a cessation of production even though the PS Glow brand is proven to be in bad faith, the United States legal system through Article 43(a) of the Lanham Act of 1946 and jurisprudence since Taylor v.  Carpenter (1846) provides a comprehensive passing off protection framework including multi-factor test, unregistered brand protection, and effective remedies systems.